Autosomal recessive Treacher Collins syndrome due to POLR1C mutations: Report of a new family and review of the literature. Issue 7 (8th April 2019) - Ghesh, Leila; Vincent, Marie; Delemazure, Anne‐Sophie; Boyer, Julie; Corre, Pierre; Perez, Fabienne; Geneviève, David; Laplanche, Jean‐Louis; Collet, Corinne; Isidor, Bertrand
Abstract : Treacher Collins syndrome (TCS) is a frequent cause of mandibulofacial dysostosis. To date, TCS‐causing mutations in three genes, namely TCOF1, POLR1D, and POLR1C have been identified. TCS is usually inherited in an autosomal dominant manner, with a high clinical variability and no phenotype–genotype correlation. Up‐to now, five families have been reported with an autosomal recessive mode of inheritance due to mutations in POLR1D or POLR1C . We report here a new family with two sisters affected by mild TCS carrying compound POLR1C heterozygous mutations, and review the literature on mild forms of TCS, autosomal recessive inheritance in this syndrome and POLR1C mutations.